Distribution of interneurons in the CA2 region of the rat hippocampus - Botcher, Nicola A.; Falck, Joanne E.; Thomson, Alex M.; Mercer, Audrey (Frontiers in Neuroanatomy, 2014)
The CA2 region of the mammalian hippocampus is a unique region with its own distinctive properties, inputs and pathologies. Disruption of inhibitory circuits in this region appears to be linked with the pathology of specific psychiatric disorders, promoting interest in its local circuitry, its role in hippocampal function and its dysfunction in disease. In previous studies, CA2 interneurones, including a novel subclass of CA2 dendrite-preferring interneurones that has not been identified in other CA regions, have been shown to display physiological, synaptic and morphological properties unique to this sub-field and may therefore play a crucial role in the hippocampal circuitry. The distributions of immuno-labelled interneurones in dorsal CA2 were studied and compared with those of interneurones in CA1 and CA3. Like those in CA1 and CA3, the somata of CA2 parvalbumin-immunoperoxidase-labeled interneurones were located primarily in Stratum Pyramidale (SP) and Stratum Oriens (SO), with very few cells in Stratum Radiatum (SR) and none in Stratum Lacunosum Moleculare (SLM). There was, however, a greater proportion of GAD-positive cells were immunopositive for PV in SP in CA2 than in CA1 or CA3. CA2 SP also contained a larger density of somatostatin-, calbindin- and VIP-immunopositive somata than CA1 and/or CA3. Like those in CA1 and CA3, CCK-immunopositive somata in CA2 were mostly located in SR. Reelin- and NPY- immunolabelled cell bodies were located in all layers of the three CA regions. However, a higher density of Reelin-positive somata was found in SP and SR of CA2 than in CA1 or CA3.